Little Angel Enterprise / Joelimmar Limbang... [et al.] - Limbang, Joelimmar; Peter, Francisca; Dallius, Deevieona Keeno (2013)
The name of our company is Little Angel Enterprise. Our business is based on partnership consist of 3 persons which have a wide knowledge on business management and really enthusiast in venturing the business world. We have chosen to open up a baby store which sells or retailed baby products such as baby’s strollers, diapers, crib, wipes, cloths, bath items, and bottle feeding items. We have decided to rent a vacant room at Level 2, Megalong Donggongon New Township, Penampang as our store location. Our operation hour will be on Monday to Friday from 09.00 am to 09.00 pm and we will also operate on Saturday but only half day which is from 09.00 am to 05.00 pm. Sunday will be the manager’s official off-day meanwhile other employees will have their off-day based on shifts. Apart from that, we have realized that there are several competitors surround our business area that offered almost the same products but as compare to them, we are offering delivery service especially for our online customer and we have also offered a membership card to be applied that bring lots of benefits especially for our loyal customer. Instead of that, we will also ensure a good customer service to our respected customer by implementing our knowledge on customer service since our academic background is tourism management which is well-known with customer-oriented industry.